THE EFFECT OF COMPENSATION ON WORK DISCIPLINE AND PERFORMANCE AMONG TEACHERS AT MTs AL-AZHAR CENTER BATURAJA - Nurlaili Nurlaili; Saipul Annur; Yuniar Yuniar (LP2M IAI Al-Khairat Pamekasan, 2026)
This study examines the effect of compensation on work discipline and teacher performance at MTs Al Azhar Center Baturaja. The research is grounded in the issue of high disciplinary expectations imposed on teachers despite relatively limited financial compensation, which may affect their professional performance and institutional sustainability. The objectives of this study are: (1) to analyze the effect of compensation on teachers’ work discipline, (2) to determine the effect of work discipline on teacher performance, and (3) to examine the direct effect of compensation on teacher performance. This research employed a quantitative approach using a verificative survey design. Data were analyzed through simple linear regression, t-tests, and the coefficient of determination (R²). The findings indicate that compensation has a positive and statistically significant effect on work discipline (t = 10.885; p < 0.05; R² = 0.656). Work discipline also has a positive and significant effect on teacher performance (t = 8.380; p < 0.05; R² = 0.531). Furthermore, compensation directly and significantly influences teacher performance (t = 5.796; p < 0.05; R² = 0.351). These findings suggest that fair and adequate financial compensation strengthens teachers’ discipline and enhances their pedagogical performance. Therefore, effective compensation management is a strategic factor in improving and sustaining teacher performance in Islamic educational institutions.